Conformational Relaxation and Kinetic Hole-Burning in Sperm Whale Myoglobin - Ansari, Anjum (1988)
Thesis (Ph.D.)--University of Illinois at Urbana-Champaign, 1988. The charge transfer band near 760nm (band III) in myoglobin (Mb) is sensitive to local heme conformation. In photodissociated MbCO at 5K, the band is red shifted with respect to the deoxy wavelength; the protein structure differs from the equilibrium deoxy structure. After photodissociation the area of band III decreases with time as the ligands rebind and the peak frequency shifts toward the deoxy value. The peak shift can be due to two different mechanisms: kinetic hole-burning and conformational relaxation. Kinetic hole-burning results from different parts of an inhomogeneously broadened spectrum rebinding with different rates. Conformational relaxation is a change in the protein structure toward the deoxy structure. An experiment by Friedman and co-workers distinguishes between the two mechanisms. Our data taken with a similar technique show that when the protein is photodissociated with a single short flash, the entire peak shift below 80K is a result of kinetic hole-burning. In sperm whale Mb the band width decreases by about 2% and the peak shift is about 7.5% of the total width after 50% of all ligands have rebound. The data are consistent with a small inhomogeneous broadening. The underlying homogeneous width is approximately 90% of the total width. We have measured the rebinding from 5K to 80K and mapped different parts of the spectrum to the distribution of rebinding enthalpies. Relaxation does occur when MbCO is exposed to a bright photolyzing light for a time greater than about 10 s, and is interpreted as local conformational relaxation of the heme and the protein structure around the heme pocket. Relaxation was measured from 10K to 120K for varying illumination times and intensities. The implications of the structural relaxation at low temperatures for the rebinding kinetics at physiological temperatures are discussed. Made available in DSpace on 2015-05-13T15:42:03Z (GMT). No. of bitstreams: 2 license.txt: 4848 bytes, ...